Analysis of the Board of Commissioners, Board of Directors, and Internal Audit on Competitiveness - Suparlan Suparlan; Nandyta Frismaya Putri; Ramlah Budiarti; Rika Apriana; Ulfa Tiana (International Journal of Economics, Management and Accounting, 2024)
This study aims to examine the influence of the board of commissioners, board of directors, and internal audit on the company's competitiveness. Where, the company's competitiveness in question is ROA, CAR and BOPO. This study used purposive sampling with a sample size of 15 banking companies listed on the Indonesian Stock Exchange in 2021-2023. The results of this study indicate that the Board of Commissioners does not affect the company's competitiveness with ROA, BOPO and CAR indicators. The board of directors does not affect the company's competitiveness with ROA, BOPO, and CAR indicators. Internal Audit does not affect the company's competitiveness with ROA, BOPO, and CAR indicators. However, the Board of Commissioners, Board of Directors, and Internal Audit affect the company's competitiveness together with the BOPO indicator. This indicates that the Board of Commissioners, Board of Directors, and Internal Audit can increase the company's competitiveness together by streamlining its operational costs and operating income.